Exploring the conditions of employment of Auxiliary Child and Youth Care Workers in Non-Profit Organisations in Soweto Funded by the Gauteng Department of Social Development - Ndima, Jabulile (University of the Witwatersrand, Johannesburg, 2025)
Non-Profit Organisations (NPOs) collaborate with the government, specifically the Department of Social Development (DSD) to provide psychosocial support services to many communities. Furthermore, this partnership also enables employees of NPOs to get skills development programs such as Child and youth care work (ACYCW) learnerships. DSD has a learnership program for developing the capacity of (ACYCW and strengthening the response to many social ills addressed by DSD and NPOs. The intention ACYCW of the learnership is absorption into employment with NPOs. This study aims to explore the conditions of employment of ACYCW in NPOs in Soweto. The study employed a qualitative research approach. The research design adopted was a multiple case study design meant to gather an in-depth understanding of the conditions of employment of ACYCWs in NPOs in Soweto. The population from which the sample was drawn consisted of ten workers working at two NPOs located in Soweto and funded by the Gauteng Department of Social Development. Purposive sampling technique was utilised for the sampling process. The data collection method used was the semi-structured interviews using an interview guide. Thematic analysis was used to analyse the data collected from this study. The findings of the study were that indeed ACYCWs do have challenges within their employment, and they highlighted inadequate resources and salaries as main key issues. The findings of this study are that ACYCWs should be prioritised especially in terms of resource allocations to cater for their low salaries and ensure that they are always supervised by qualified ACYCWs
A research report submitted in fulfillment of the requirements for the Master of Arts, in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Auxiliary Child and Youth Care Work; Non-Profit Organisation; Employment conditions; Funded; Department of Social Development; SDG-8: Decent work and economic growth; SDG-16: Peace, justice and strong institutions